2004
DOI: 10.1038/sj.npp.1300383
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Lithium-Regulated Genes in Cultured Lymphoblasts of Lithium Responsive Subjects with Bipolar Disorder

Abstract: Lithium, a common drug for the treatment of bipolar disorder (BD), requires chronic administration to prevent recurrences of the illness. The necessity for long-term treatment suggests that changes in genes expression are involved in the mechanism of its action. We studied effects of lithium on gene expression in lymphoblasts from BD patients, all excellent responders to lithium prophylaxis. Gene expression was analyzed using cDNA arrays that included a total of 2400 cDNAs. We found that chronic lithium treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…[131][132][133][134] In addition to the studies of PDE4s in brain, PDE4 expression is modulated by lithium in lymphoblastoid cell lines derived from lithium-responsive patients with bipolar disorder. 135 These effects may be interpreted as meaning that the PDE4s participate in responses to therapeutic treatments, or alternatively, as providing further confirmation of PDE4 involvement in causing illness. Nicotine has also been shown to influence brain expression of PDE4s, causing dose-dependent decreases in the hippocampus, PFC and nucleus accumbens.…”
Section: Pde4b As a Risk Factor For Psychiatric Illness: Interaction mentioning
confidence: 99%
“…[131][132][133][134] In addition to the studies of PDE4s in brain, PDE4 expression is modulated by lithium in lymphoblastoid cell lines derived from lithium-responsive patients with bipolar disorder. 135 These effects may be interpreted as meaning that the PDE4s participate in responses to therapeutic treatments, or alternatively, as providing further confirmation of PDE4 involvement in causing illness. Nicotine has also been shown to influence brain expression of PDE4s, causing dose-dependent decreases in the hippocampus, PFC and nucleus accumbens.…”
Section: Pde4b As a Risk Factor For Psychiatric Illness: Interaction mentioning
confidence: 99%
“…22,23 The effect of lithium on gene expression was also investigated in immortalized lymphocytes from bipolar disorder patients. 24 However, only a few microarray analysis using immortalized lymphocytes from patients with schizophrenia have been reported. [25][26][27] Whether immortalized lymphocytes are an appropriate alternative to neuronal tissue remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Lithium has been shown to increase the expression of the antiapoptotic gene BCL2 [4] and also to increase cAMP-responsive element-/binding protein-mediated gene transcription [5]. More recently, microarray techniques have been applied to study the effects of lithium on mouse brain [6,7], rat brain [8], and in human neuronal or peripheral blood cell lines [9,10,11,12,13]. These studies have reported effects of lithium on the expression of a number of genes involved in ion channel and receptor function, signal transduction (including the phosphatidylinositol system), neuroprotective mechanisms, endothelial growth factor, energy metabolism, and thyroid function.…”
Section: Introductionmentioning
confidence: 99%